Nanometer sheet-shaped lithium zirconium phosphate self-supporting composite solid electrolyte

Through the composite preparation of nanosheet lithium zirconium phosphate and polymer electrolyte, the safety and conductivity problems of liquid electrolytes in lithium-ion batteries are solved, and a high-performance solid-state battery is realized, which significantly improves the circulation performance and use of lithium-ion batteries. life.

CN119253028AInactive Publication Date: 2025-01-03HEYUAN LICHUANG (SUZHOU) NEW ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411337410.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional liquid electrolytes have risks of leakage, explosion, and problems of low ionic conductivity and high interfacial impedance in lithium-ion batteries, and there is no application of nanosheet-shaped oxide solid electrolyte as an inorganic filler.

Method used

The self-supported composite solid electrolyte is prepared by combining nanosheet lithium zirconium phosphate with polymer electrolyte, and the nanosheet lithium zirconium phosphate self-supported composite solid electrolyte is prepared by thermal coating method to improve ionic conductivity and be applied to lithium-ion solid batteries.

Benefits of technology

It significantly improves the circulation performance and service life of lithium-ion batteries, has excellent electrochemical performance, can cycle for 1000 cycles at 3C, with a capacity retention rate of 86%, and an ionic conductivity of 1.6×10-4S/cm at 60 ℃. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253028A_ABST
    Figure CN119253028A_ABST
Patent Text Reader

Abstract

The invention discloses a nanometer sheet-shaped lithium zirconium phosphate self-supported composite solid electrolyte, and belongs to the technical field of battery materials, the nanometer sheet-shaped lithium zirconium phosphate self-supported composite solid electrolyte comprises a lithium salt, a polymer and nanometer sheet-shaped lithium zirconium phosphate, and a preparation method of the composite solid electrolyte comprises the following steps: dissolving the polymer and the lithium salt in an organic solvent; the preparation method comprises the following steps of: adding nano sheet-shaped lithium zirconium phosphate after complete dissolution, uniformly stirring, then coating on a polytetrafluoroethylene film, and drying in a glove box, so as to obtain the nano sheet-shaped lithium zirconium phosphate self-supported composite solid electrolyte with the thickness of about 70 microns after the solvent is volatilized, thereby obtaining the nano sheet-shaped lithium zirconium phosphate self-supported composite solid electrolyte with the thickness of about 70 microns. The composite electrolyte has good safety performance and relatively high ionic conductivity and lithium ion transference number, and a LiFePO4 / / Li battery assembled by using the composite electrolyte can stably circulate for 1000 circles at high magnification of 3C, and has stable coulombic efficiency and relatively high capacity retention ratio. The invention provides a composite solid electrolyte with excellent performance for the field of lithium ion solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte. Background Art

[0002] With the rise of new energy electric vehicles and flexible wearable electronic products, the requirements for batteries are getting higher and higher, not only requiring high energy density and long service life, but also high safety. Traditional electrolytes are generally liquid electrolytes, which are prone to safety accidents such as leakage and explosion. Nowadays, using solid electrolytes to replace traditional liquids is a very good choice. It can not only improve safety performance and battery energy density, but also effectively prevent the growth of lithium dendrites in lithium-ion batteries and reduce battery short circuit problems.

[0003] Composite solid electrolytes combine inorganic solid electrolytes and polymer electrolytes, effectively solving the problems of low ion conductivity and high interface impedance of solid-state lithium-ion batteries. This is mainly because the interaction between inorganic solid electrolytes and polymers can significantly reduce the crystallinity of polymers and promote the dissociation of lithium ions; at the same time, inorganic solid electrolytes can also provide new lithium ion transmission channels and improve lithium ion transmission efficiency.

[0004] The size and shape of inorganic fillers have a critical influence on the interface between fillers and polymers. Controlling the size and shape of inorganic fillers can improve the transmission efficiency of lithium ions, thereby increasing lithium ion conductivity and reducing interface impedance, and obtaining solid-state lithium batteries with better electrochemical performance. At present, there are a large number of reports on the use of inorganic nanosheets as polymer fillers to prepare composite solid electrolytes, but there are no reports on nanosheet oxide solid electrolytes as inorganic fillers. Summary of the invention

[0005] In view of the above-mentioned shortcomings, the present invention discloses a nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte. Nano-sheet lithium zirconium phosphate is composited with a polymer electrolyte to prepare a self-supporting composite solid electrolyte, which effectively improves the ionic conductivity of the composite solid electrolyte. The self-supporting composite solid electrolyte is applied to solid-state lithium batteries, greatly improving the cycle performance and service life of the battery.

[0006] The present invention includes the following technical solutions: A nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte is made of lithium salt, polymer and nano-sheet lithium zirconium phosphate; the nano-sheet lithium zirconium phosphate is a rhombohedral phase structure, with a lateral size of 100-400 nm and a thickness of 20-100 nm.

[0007] Furthermore, the method for preparing the above-mentioned nano-sheet-like lithium zirconium phosphate self-supporting composite solid electrolyte comprises the following steps: S1: weighing lithium salt and polymer in a certain ratio, dissolving them in an organic solvent to prepare a solution; S2: adding a certain proportion of nano-sheet lithium zirconium phosphate to the solution in S1, heating and stirring to obtain a uniform slurry; S3: The slurry prepared in S2 is evenly coated on a polytetrafluoroethylene film with a certain thickness, dried in an oven, and then stored in a glove box.

[0008] Furthermore, in the above preparation method, in step S1, the lithium salt is selected from LiPF 6 、LiClO 4 Or one or more of LiTFSI.

[0009] Furthermore, in the above preparation method, in step S1, the polymer is selected from one or more of polycaprolactone (PCL), polyethylene oxide (PEO) or polyvinylidene fluoride (PVDF).

[0010] Furthermore, in the above preparation method, in step S1, the molar ratio of the lithium salt to the oxygen atoms in the polymer is n (Li + ): n (O)=1:20.

[0011] Furthermore, in the above preparation method, in step S1, the organic solvent is selected from one or more of dimethyl carbonate (DMC), anhydrous acetonitrile or N-methylpyrrolidone (NMP); preferably, the lithium salt and the polymer are dissolved in the above organic solvent at a solid mass ratio of 5-20wt%.

[0012] Furthermore, in the above preparation method, in step S2, the stirring temperature is 60° C. and the speed is 500 r / min.

[0013] Furthermore, in the above preparation method, in step S2, the nano-sheet lithium zirconium phosphate has a rhombohedral phase structure, a lateral size of 100-400 nm, and a thickness of 20-100 nm.

[0014] Furthermore, in the above preparation method, in step S2, the mass ratio of the nano-sheet lithium zirconium phosphate to the polymer is 0.31-0.83:1.

[0015] Furthermore, in the above preparation method, in step S3, the coating thickness is 500-1500 μm, and the thickness after drying is about 70 μm.

[0016] The invention also discloses the application of the nano-sheet-like lithium zirconium phosphate self-supporting composite solid electrolyte or the preparation method in the preparation of lithium-ion solid-state batteries.

[0017] Compared with the prior art, the present invention has the following outstanding beneficial effects: The invention discloses a nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte and a preparation method thereof. Firstly, a nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte is prepared by a thermal coating method, wherein the PCL-based composite solid electrolyte has a high ionic conductivity of 1.6×10 -4 S / cm, and the lithium ion transference number also reached 0.78. Assembling LiFePO with nanosheet lithium zirconium phosphate self-supporting composite solid electrolyte 4 / / Li battery can cycle for 1000 times at 3C rate, with a capacity retention rate of 86%, and the electrochemical performance is much better than that of composite solid electrolyte based on non-nano-sheet lithium zirconium phosphate. The present invention provides a composite solid electrolyte with excellent performance in the field of lithium-ion solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The temperature-dependent conductivity diagram of the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte obtained in Example 1 and Comparative Examples 1 and 2; Figure 2 This is a time-current curve of the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1; Figure 3 LSV diagrams of nano-sheet lithium zirconium phosphate self-supporting composite solid electrolytes obtained in Example 1 and Comparative Examples 1 and 2; Figure 4 3C long cycle performance diagram of the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1 and Comparative Examples 1 and 2; Figure 5 The rate performance diagram of the nano-sheet-like lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1 and Comparative Examples 1 and 2; Figure 6 This is a surface SEM image of the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte obtained in Example 1; Figure 7 This is a schematic diagram of the nanosheet-like lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 The process of preparing the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte in this embodiment is as follows: 0.144 g LiTFSI, 0.57 g PCL and 5 mL DMC solvent were placed in a closed vial and stirred at 60 °C. When PCL was completely dissolved, 0.306 g of nanosheet lithium zirconium phosphate with a rhombohedral phase structure, a lateral size of 100-400 nm and a thickness of 20-100 nm was added. Stirring was continued for 12 h, ultrasonicated for 30 min, and coated on a polytetrafluoroethylene film with a coating thickness of 600 μm. The film was placed in a glove box for drying. After drying, the film was cut into discs with a diameter of 15 mm and assembled into batteries for performance testing.

[0021] Among them, nano-sheet lithium zirconium phosphate can be obtained by high-energy ball milling of rhombohedral lithium zirconium phosphate powder. The recommended process of high-energy ball milling is: the ball milling medium is anhydrous ethanol, the ball milling beads are made of zirconium oxide, the size is 0.2~0.3 mm in diameter, the mass of the ball milling beads is 50~60 times the mass of the powder, the ball mill speed is 2000~3000 r / min, and the ball milling time is 8~15 h.

[0022] Example 2 The process of preparing the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte in this embodiment is as follows: 0.144 g LiTFSI, 0.57 g PCL and 5 mL DMC solvent were placed in a closed vial and stirred at 60 °C. When PCL was completely dissolved, 0.178 g of nanosheet lithium zirconium phosphate with a rhombohedral phase structure, a lateral size of 100-400 nm and a thickness of 20-100 nm was added. Stirring was continued for 12 h, ultrasonicated for 30 min, and coated on a polytetrafluoroethylene film with a coating thickness of 600 μm. The film was placed in a glove box for drying. After drying, the film was cut into discs with a diameter of 15 mm and assembled into batteries for performance testing.

[0023] Example 3 The process of preparing the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte in this embodiment is as follows: 0.144 g LiTFSI, 0.57 g PCL and 5 mL DMC solvent were placed in a closed vial and stirred at 60 °C. When PCL was completely dissolved, 0.475 g of nanosheet lithium zirconium phosphate with a rhombohedral phase structure, a lateral size of 100-400 nm and a thickness of 20-100 nm was added. Stirring was continued for 12 h, ultrasonicated for 30 min, and coated on a polytetrafluoroethylene film with a coating thickness of 600 μm. The film was placed in a glove box for drying. After drying, the film was cut into discs with a diameter of 15 mm and assembled into batteries for performance testing.

[0024] Comparative Example 1 In this comparative example, a self-supporting composite solid electrolyte of lithium zirconium phosphate electrolyte is prepared. The lithium zirconium phosphate used is nanoparticles with a particle size of 200 nm. Other parts are the same as those in Example 1.

[0025] Comparative Example 2 In this comparative example, a self-supporting composite solid electrolyte of lithium zirconium phosphate electrolyte is prepared. The lithium zirconium phosphate used is particles with a particle size of 2 μm. Other parts are the same as those in Example 1.

[0026] Test Example 1 The temperature-dependent conductivity of the lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1, Comparative Example 1 and Comparative Example 2 was tested. The results are as follows: Figure 1 The results show that the ionic conductivity of Example 1 is higher than that of the comparative example at different temperatures, reaching 1.6×10 -4 S / cm.

[0027] Test Example 2 The time-current curve of the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1 is as follows: Figure 2 The calculated lithium ion migration number is 0.78.

[0028] Test Example 3 The LSV of the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1 and Comparative Example 1 and Comparative Example 2 was tested. Figure 3 The results show that the electrochemical stability window of Example 1 is 5.52 V, which is higher than that of the comparative example.

[0029] Test Example 4 The 3C long cycle performance of the nano-sheet-like lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1 and Comparative Example 1 and Comparative Example 2 was tested. Figure 4 The results show that Example 1 can be cycled stably at 3C for 1000 cycles, with a capacity retention rate of 86%.

[0030] Test Example 5 The rate performance of the nano-sheet-like lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1 and Comparative Example 1 and Comparative Example 2 was tested. Figure 5 The results show that Example 1 has the best rate performance, and there is no capacity decay or battery short circuit at 3C.

[0031] Test Example 6 The surface SEM image of the nano-sheet-like lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Test Example 1 is as follows: Figure 6 The results show that the surface is flat and smooth, and nano-lithium zirconium phosphate agglomerates in a small area.

[0032] Test Example 7 The schematic diagram of the structure of the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte prepared in Example 1 is as follows: Figure 7 shown.

[0033] It can be seen from the above embodiments that the present invention discloses a nano-sheet-like lithium zirconium phosphate self-supporting composite solid electrolyte and a preparation method thereof. First, a nano-sheet-like lithium zirconium phosphate self-supporting composite solid electrolyte is prepared by a thermal coating method, wherein the PCL-based composite solid electrolyte has a high ionic conductivity of 1.6×10 -4 S / cm, and the lithium ion transference number also reached 0.78. Assembling LiFePO with nanosheet lithium zirconium phosphate self-supporting composite solid electrolyte 4 / / Li battery can be cycled for 1000 cycles at 3C rate, with a capacity retention rate of 86%. The electrochemical performance is much better than that of composite solid electrolyte based on non-nano-sheet lithium zirconium phosphate. The present invention provides a composite solid electrolyte with excellent performance in the field of lithium-ion solid-state batteries. The above are only a few preferred embodiments of the present invention, which are described in a more specific and detailed manner, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte, characterized in that: It is made of lithium salt, polymer and nano-sheet lithium zirconium phosphate; the nano-sheet lithium zirconium phosphate has a rhombohedral phase structure, a lateral size of 100-400 nm and a thickness of 20-100 nm.

2. The method for preparing the nano-sheet lithium zirconium phosphate self-supporting composite solid electrolyte according to claim 1, characterized in that: The following steps are involved: S1: weighing lithium salt and polymer in a certain ratio, dissolving them in an organic solvent to prepare a solution; S2: adding a certain proportion of nano-sheet lithium zirconium phosphate to the solution in S1, heating and stirring to obtain a uniform slurry; S3: The slurry prepared in S2 is evenly coated on a polytetrafluoroethylene film with a certain thickness, dried in an oven, and then stored in a glove box.

3. The preparation method according to claim 2, characterized in that: In step S1, the lithium salt is selected from one or more of LiPF6, LiClO4 or LiTFSI.

4. The preparation method according to claim 2, characterized in that: In step S1, the polymer is selected from one or more of polycaprolactone (PCL), polyethylene oxide (PEO) or polyvinylidene fluoride (PVDF).

5. The preparation method according to claim 2, characterized in that: In step S1, the molar ratio of the lithium salt to the oxygen atoms in the polymer is n (Li + ): n (O)=1:

20.

6. The preparation method according to claim 2, characterized in that: In step S1, the organic solvent is selected from one or more of dimethyl carbonate (DMC), anhydrous acetonitrile or N-methylpyrrolidone (NMP); the lithium salt and the polymer are dissolved in the organic solvent at a solid mass ratio of 5-20wt%.

7. The preparation method according to claim 2, characterized in that: In step S2, the stirring temperature is 60°C and the stirring speed is 500 r / min.

8. The preparation method according to claim 2, characterized in that: In step S2, the nano-sheet lithium zirconium phosphate has a rhombohedral phase structure, a lateral size of 100-400 nm, and a thickness of 20-100 nm; the mass ratio of the nano-sheet lithium zirconium phosphate to the polymer is 0.31-0.83:

1.

9. The preparation method according to claim 2, characterized in that: In step S3, the coating thickness is 500-1500 μm, and the thickness after drying is about 70 μm.

10. Use of the preparation method according to claims 2-9 in the preparation of lithium-ion solid-state batteries.

Citation Information

Patent Citations

  • High-power composite solid electrolyte based on polycaprolactone self-repairing and preparation method thereof

    CN114447422A

  • High-conductivity battery electrolyte, preparation method thereof and solid-state lithium-sulfur battery

    CN117276639A

  • Self-supporting composite solid electrolyte as well as preparation method and application thereof

    CN117728004A

  • Method for improving performance of solid electrolyte

    CN117913387A

  • Nanometer sheet-shaped lithium zirconium phosphate solid electrolyte as well as preparation method and application thereof

    CN118693337A